Makna Dan Relevansi Penderitaan Salib Kristus - Frits Octavianus Tatilu (TEMISIEN: Jurnal Teologi, Misi, dan Entrepreneurship, 2021)
The article entitled "The PurposeMeaning of the Passion of the Cross of Christ And Its Relevance" focuses on how the cross has a powerful meaning in the atonement of Christ. With a strong narrative, Matthew reveals the purpose of Christ's suffering on the cross. With his narrative also Matthew shows the purpose of Christ's suffering through the events that took place around the cross in Golgotha. Therefore, the sufferings of Christ have relevance in the life of the believer. In this article, the author describes the relevance of the meaning of Christ's suffering on the cross according to Matthew 27: 45-54. AbstrakArtikel yang berjudul “Makna Penderitaan Salib Kristus Dan Relevansinya” ini berfokus pada bagaimana salib memiliki makna yang kuat di dalam penebusan Kristus. Dengan narasi yang kuat Matius mengungkapkan tujuan penderitaan Kristus di atas kayu salib. Dengan narasinya pula Matius menunjukkan tujuan penderitaan Kristus melalui peristiwa-peristiwa yang terjadi di seputar peristiwa salib di Golgota. Karena itu, penderitaan Kristus memiliki relevansi dalam kehidupan orang percaya. Dalam artikel ini, penulis menguraikan relevansi dari makna penderitaan Kristus di atas kayu salib menurut Matius 27:45-54.